2021
DOI: 10.1016/j.paid.2020.110348
|View full text |Cite
|
Sign up to set email alerts
|

Trait emotional intelligence and emotional experiences during the COVID-19 pandemic outbreak in Poland: A daily diary study

Abstract: The study examined trait emotional intelligence as a predictor for emotional reactions experienced during the first full week of the lockdown in Poland (from 16th to 22nd March). One hundred and thirty persons (101 women and 25 men; 4 did not report their gender)participated in the baseline measurement of trait emotional intelligence, positive and negative affect, and affect intensity and in a one-week daily diary. Trait emotional intelligence correlated positively with baseline positive affect and positive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
112
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(149 citation statements)
references
References 83 publications
15
112
0
9
Order By: Relevance
“…The discrete negative emotions approach is more informative for describing the emotional impacts of the COVID-19 pandemic compared with the overall measurement of negative emotions (Moron and Biolik-Moron 2021). Consistent with recent studies (Li et al 2020;Moron and Biolik-Moron 2021;Wang et al 2021), our results showed that the levels of fear and anger during the COVID-19 pandemic were signi cantly higher than those before. However, it should be noted that the enhanced fear and anger during the epidemic are likely derived from different sources.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The discrete negative emotions approach is more informative for describing the emotional impacts of the COVID-19 pandemic compared with the overall measurement of negative emotions (Moron and Biolik-Moron 2021). Consistent with recent studies (Li et al 2020;Moron and Biolik-Moron 2021;Wang et al 2021), our results showed that the levels of fear and anger during the COVID-19 pandemic were signi cantly higher than those before. However, it should be noted that the enhanced fear and anger during the epidemic are likely derived from different sources.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, the data collection for the during-COVID-19 variables was only during the Spring Festival. Men are more likely than women to enjoy leisure time on holidays (Moron and Biolik-Moron 2021), which may explain their lower overall negative emotions in our study. However, these are speculations, and the role of other variables in this gender difference, such as coping strategies and emotional regulation during the COVID-19 pandemic, needs to be further examined.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations